1982
DOI: 10.1111/j.1365-2141.1982.tb01947.x
|View full text |Cite
|
Sign up to set email alerts
|

Size dependent platelet subpopulations: relationship of platelet volume to ultrastructure, enzymatic activity, and function

Abstract: A method for the separation of platelets on the basis of their size has been developed using counterflow centrifugation. Platelets were separated, free of plasma proteins and other cells, into seven subpopulations. The smallest-sized platelets, designated as Fraction 1, had a mean platelet volume (MPV) of 3.94 +/- 0.60 micrometer 3 (SD). Each successive fraction had a progressively larger MPV. The MPV for the largest-sized platelets, designated Fraction 7, was 8.19 +/- 0.64 micrometer 3. The MPV for the origin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
223
1
9

Year Published

1984
1984
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 363 publications
(234 citation statements)
references
References 29 publications
1
223
1
9
Order By: Relevance
“…Larger platelets are more reactive, producing higher levels of ADP, β-thromboglobulin, and thromboxane B 2 [20][21][22], and aggregate more in response to a fixed dose of ADP and collagen [20,21]. Based on these reports [20][21][22], the significant positive correlation between MPV and number of PA observed in this study implied that PA count in our system may have reflected platelet reactivity.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Larger platelets are more reactive, producing higher levels of ADP, β-thromboglobulin, and thromboxane B 2 [20][21][22], and aggregate more in response to a fixed dose of ADP and collagen [20,21]. Based on these reports [20][21][22], the significant positive correlation between MPV and number of PA observed in this study implied that PA count in our system may have reflected platelet reactivity.…”
Section: Discussionmentioning
confidence: 55%
“…Based on these reports [20][21][22], the significant positive correlation between MPV and number of PA observed in this study implied that PA count in our system may have reflected platelet reactivity. Therefore, the consistently lower PA count in addition to lower degree of fall in platelet count in the blood of pregnant women than in non-pregnant women in this study strongly suggested that platelet reactivity is reduced in early pregnancy, consistent with results of the previous study by Burke et al [19].…”
Section: Discussionmentioning
confidence: 93%
“…Mean platelet volume (MPV) is a marker of platelet size and activation, and its increased level reflects active large platelets. Some clinical studies have shown that active large platelets contain denser granules, which are metabolically and enzymatically more active than small ones and have a higher thrombotic potential [6]. Increased MPV has been found to be related with mortality after following acute myocardial infarction and restenosis [7], and this finding has been reported in hypertension background [8].…”
Section: Introductionmentioning
confidence: 61%
“…The effects of an over-activated sympathetic nervous system on the haemostatic system occur in two ways. First, platelet activation via alpha2-adrenoreceptor stimulation which [24] causes shape change and thereby increases MPV [25,26]. Second, larger, activated platelets which are sequestered in the spleen [27] can be released into the circulatory system following the elevated levels of adrenaline [27] that contribute to increased MPV levels; this might be the first mechanism of how RHTN promotes the increased levels of MPV.…”
Section: Discussionmentioning
confidence: 99%
“…Stressful life events and anxiety usually elevate circulating levels of blood catecholamines. Increased catecholamine levels are thought to increase thrombosis by causing an increase in platelet activity and sympathoadrenal activation is thought to stimulate platelets through the α-2 receptors, resulting in an increase in platelet volume and activity [7,8]. It is accepted that serotonin which plays an important role in anxiety disorders is also an important factor in determining vascular tone and platelet aggregation [9].…”
Section: Introductionmentioning
confidence: 99%